A history of Brazilian economic thought
1 online resource (vi, 262 pages)
Keywords: "This book provides a comprehensive analysis of the evolution of Brazilian economic thought ranging from colonial times through to the early 21st Century. It explores the production of ideas on the Brazilian economy through various forms of publication and contemporary thoughts on economic contexts and development policies, all closely reflecting the evolution of economic history. After an editorial introduction, it opens with a discussion of the issue of the historical limits to and circumstances of the production of pure economic theory by Brazilian economists. The proceeding chapters follow the classical periodization of Brazilian economic history, starting with the colonial economy (up until the early 19th century) and the transition into an economy independent from Portugal (1808 through the 1830s) when formal independence took place in 1822. This book is ideal for international and national scholars in social sciences, students in both undergraduate and graduate courses in economics, and any individuals interested in Brazilian economic and intellectual history"--